2005
DOI: 10.1029/2004gc000826
|View full text |Cite
|
Sign up to set email alerts
|

Northern Red Sea: Nucleation of an oceanic spreading center within a continental rift

Abstract: [1] The northern Red Sea is an amagmatic continental rift in which an oceanic spreading center is beginning to develop. A new compilation of marine geophysical data permits delineation of the structure of the northern Red Sea and of the manner in which the transition from continental to oceanic extension is occurring in this rift. The margins of the northern Red Sea are formed by large, apparently active faults on the seaward edge of the narrow continental shelves. The morphology of the main trough is a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 97 publications
(246 reference statements)
10
71
1
Order By: Relevance
“…However, more recent studies (Cochran, 2005;Cochran and Karner, 2007) report clear axial depression of the bathymetry and aligned magnetic anomalies as well as a chain of dykes that are more typical for rifting processes. In our study, we can see that the high-velocity anomaly in the Red Sea has very sharp bounds coinciding with the coastline; this presumes an abrupt difference in crustal properties between the onshore and offshore areas at all depth intervals.…”
Section: Oceanic Crust In the Red Seamentioning
confidence: 99%
“…However, more recent studies (Cochran, 2005;Cochran and Karner, 2007) report clear axial depression of the bathymetry and aligned magnetic anomalies as well as a chain of dykes that are more typical for rifting processes. In our study, we can see that the high-velocity anomaly in the Red Sea has very sharp bounds coinciding with the coastline; this presumes an abrupt difference in crustal properties between the onshore and offshore areas at all depth intervals.…”
Section: Oceanic Crust In the Red Seamentioning
confidence: 99%
“…Dredging samples and side-scan images indicate that the spreading center is associated with volcanic features, basaltic rocks and gabbros (Monin et al 1982;Cochran 1983;Cochran 2005;Cochran & Karner 2007, Mitchell et al 2010. Some of the recent presalt exploratory boreholes in the South Atlantic, drilled in regions close the continent-ocean edge, have also penetrated basalts and gabbros (Mohriak, 2011).…”
mentioning
confidence: 99%
“…The floor of the Gulf of Suez is quite smooth and the depth of water is shallow, averaging about 55 m. In contrast, the Gulf of Aqaba has varied bottom topography with much greater depths of water reaching 1460 m. The bathymetry of the active, main trough of the northern Red Sea rift, consists of a series of terraces stepping down to an axial depression at a depth of 1100-1200 m (Martinez and Cochran, 1988;Cochran, 2005). Sediment deformation within the axial depression is much more intense than in the remainder of the Red Sea (Knott et al, 1966;Guennoc et al, 1988;Martinez and Cochran, 1988), implying that tectonic activity and extension is presently concentrated predominantly in the axial depression.…”
Section: Topographic and Free Air Gravity Anomaly Of The Northern Redmentioning
confidence: 99%
“…Based on the geophysical data in the Northern Red Sea, Cochran (2005) suggested that rift development occurs via the rotation of large crustal fault blocks that sole into a zone of plastic creep in the lower crust, resulting in a flat Moho and high upper crustal relief. Initial broadly distributed extension is eventually replaced by focused extension at the rift axis leading to rapid lithospheric thinning and melt generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation